Komunikasi Asertif dan Penggunaan Media Sosial dalam Menghadapi Dunia Usaha dan Dunia Kerja - Widhi Rachmawati, Diana; Novianti, Teni; Kusumaningrum, Arini; Sofyan, Hady; Mulyeni, Sri; Herlina, Herlina (BADAN PENERBIT STIEPARI PRESS, 2025)
Communication is one of the key competencies in the business modern and workplace for young generation. Good communication skills, especially assertive communication, allow individuals to convey ideas, feelings, and needs clearly without violating the rights of others. On the other hand, social media as a digital platform has become the main means of interaction and self-expression for the younger generation. This community service activity is to provide an understanding of assertive communication and the use of social media can contribute to improving students' communication skills in facing business world and the world of work. Participants in this training activity numbered 60 students of SMK Tunas Bangsa West Bandung. After the training material was delivered, there was an increase in participants' understanding and knowledge in the use of social media and assertive communication, after receiving training, participants were more confident in communicating, expressing ideas and being able to accept criticism well. Participants' interest in creating good personal branding on social media became higher, participants' knowledge, and skills in creating a positive digital footprint increased.